The effects of pre-salting methods on salt and water distribution of heavily salted cod, as analyzed by H-1 and Na-23 MRI, Na-23 NMR, low-field NMR and physicochemical analysis - Gudjónsdóttir, María; Traore, Amidou; Karlsdóttir, Magnea Gudrún; Arason, Sigurjón (Food Chemistry, 2015)
International audience The effect of different pre-salting methods (brine injection with salt with/without polyphosphates, brining and pickling) on the water and salt distribution in dry salted Atlantic cod (Gadus morhua) fillets was studied with proton and sodium NMR and MRI methods, supported by physicochemical analysis of salt and water content as well as water holding capacity. The study indicated that double head brine injection with salt and phosphates lead to the least heterogeneous water distribution, while pickle salting had the least heterogeneous salt distribution. Fillets from all treatments contained spots with unsaturated brine, increasing the risk of microbial denaturation of the fillets during storage: Since a homogeneous water and salt distribution was not achieved with the studied pre-salting methods, further optimizations of the salting process, including the pre-salting and dry salting steps, must be made in the future.